Blue carbon inventories of Spain and Portugal for their inclusion in national climate mitigation strategies - Nerea Piñeiro-Juncal; Oscar Serrano; Carmen B. de los Santos; Nuria Marbà; Elena Díaz-Almela; Fernando Tuya; Inés Mazarrasa; Joxe Mikel Garmendia; Xosé Lois Otero; Karina Inostroza; Jordi F. Pagès; Gonzalo Mendez-Martínez; et al. (Marine Pollution Bulletin, 2026)

Dissecting the role of mineralocorticoid receptors in binge-like alcohol drinking in mice: Finerenone as a potential pharmacotherapy - Courtney S. Wilkinson; Nicolaus Bruns; Claire L. Pince; M. Adrienne McGinn; Mehdi Farokhnia; Lorenzo Leggio; Leandro F. Vendruscolo (Psychopharmacology, 2026)

Temporal evolution of the performance evaluation of the laboratories at Spanish nuclear power plants in water samples - José Antonio Suárez-Navarro; Virginia Peyres; Ana Isabel Sánchez-Cabezudo; Nuria Navarro; Victor Manuel Expósito-Suárez; Jordi Español; José Manuel Arteaga; Manuel Brun; Rosaura Miret; Ana Llorente; Mercedes Ibañez; J. F. Benavente (Environmental Monitoring and Assessment, 2025)
This study examined the performance evaluation and analysis of the laboratories of Spanish Nuclear Power Plants over the last 9 years of the 34 editions organized by CIEMAT. The participating nuclear power plants were Almaraz, Ascó I, Ascó II, Cofrentes, Santa María de Garoña, Trillo, and Vandellós II. The radionuclides analyzed were those necessary to ensure operational radiological protection and the control of liquid effluents from a nuclear power plant. The radionuclides are classified into beta emitters: 3 H, 14 C, and 90 Sr, and gamma emitters: 241 Am, 57 Co, 137 Cs, and 60 Co. The results of the z score showed that the performance in determining 3 H was 100% satisfactory in most years, except in 2010 and 2014, where percentages of 83% and 87.5% were recorded, respectively. 90 Sr showed greater variability with a satisfaction range between 60 and 100%. Furthermore, the gamma emitters achieved satisfactory evaluations above 93% within the studied time range. The analysis of the distributions of the relative differences between the laboratory results and the reference values confirmed that the distributions were normal according to the Shapiro–Wilk test, with a percentage of outlier values below 5%. Additionally, linear regression analysis was used to evaluate the dispersion of the results relative to the reference values through the RSE parameter, being highest for 3 H and 14 C. The PomPlot graphs allowed for the visualization of the relationship between the obtained results and the reference values, indicating that, although high percentages of satisfactory evaluations were achieved, certain trends in the laboratory results must be considered to detect potential future deviations in the analytical methodologies.

Calibration of visible and near-infrared spectral imaging technology to predict the quality evolution of retail fresh pork bellies with different fat content - Michela Albano-Gaglio; Carlos A. Esquerre; Colm P. O’Donnell; Israel Muñoz; Gamal ElMasry; Maria Font-i-Furnols; Juan F. Tejeda; Albert Brun; Elsa Lloret; Begonya Marcos (Food Research International, 2025)

Patch age alters seagrass response mechanisms to herbivory damage - Rocío Jiménez-Ramos; Luis G. Egea; Claudia J. Pérez-Estrada; Eduardo F. Balart; Juan J. Vergara; Fernando G. Brun (Marine Environmental Research, 2024)

Diversity and seasonal variation of the molluscan community associated with the seagrass Halodule wrightii in a marine protected area in the southern Gulf of California - C. J. Pérez-Estrada; R. Rodríguez-Estrella; F. G. Brun-Murillo; P. Gurgo-Salice; R. Valles-Jiménez; E. Morales-Bojórquez; M. A. Medina-López (Aquatic Ecology, 2023)

Effects of DPTQ, a novel positive allosteric modulator of the dopamine D1 receptor, on spontaneous eye blink rate and spatial working memory in the nonhuman primate - Stacy A. Castner; Linli Zhang; Charles R. Yang; Junliang Hao; Jeffrey W. Cramer; Xushan Wang; Robert F. Bruns; Hugh Marston; Kjell A. Svensson; Graham V. Williams (Psychopharmacology, 2023)
Rationale Dopamine (DA) signaling through the D1 receptor has been shown to be integral to multiple aspects of cognition, including the core process of working memory. The discovery of positive allosteric modulators (PAMs) of the D1 receptor has enabled treatment modalities that may have alternative benefits to orthosteric D1 agonists arising from a synergism of action with functional D1 receptor signaling. Objectives To investigate this potential, we have studied the effects of the novel D1 PAM DPTQ on a spatial delayed response working memory task in the rhesus monkey. Initial studies indicated that DPTQ binds to primate D1R with high affinity and selectivity and elevates spontaneous eye blink rate in rhesus monkeys in a dose-dependent manner consistent with plasma ligand exposures and central D1activation. Results Based on those results, DPTQ was tested at 2.5 mg/kg IM in the working memory task. No acute effect was observed 1 h after dosing, but performance was impaired 48 h later. Remarkably, this deficit was immediately followed by a significant enhancement in cognition over the next 3 days. In a second experiment in which DPTQ was administered on days 1 and 5, the early impairment was smaller and did not reach statistical significance, but statistically significant enhancement of performance was observed over the following week. Lower doses of 0.1 and 1.0 mg/kg were also capable of producing this protracted enhancement without inducing any transient impairment. Conclusions DPTQ exemplifies a class of D1PAMs that may be capable of providing long-term improvements in working memory.

Skeletal and cardiac muscle have different protein turnover responses in a model of right heart failure - Danielle R. Bruns; Benjamin D. McNair; Frederick F. Peelor; Agnieszka K. Borowik; Atul Pranay; Aykhan Yusifov; Benjamin F. Miller (GeroScience, 2023)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Cardiac response to adrenergic stress differs by sex and across the lifespan - Aykhan Yusifov; Vikram E. Chhatre; Jacob M. Zumo; Ross F. Cook; Benjamin D. McNair; Emily E. Schmitt; Kathleen C. Woulfe; Danielle R. Bruns (GeroScience, 2021)

Marine fish diversity in Tropical America associated with both past and present environmental conditions - Andrea Polanco F.; Fabian Fopp; Camille Albouy; Philipp Brun; Lydian Boschman; Loïc Pellissier (Journal of Biogeography, 2020)
Aim Tropical America, including the Tropical Eastern Pacific and the Caribbean Sea, presents a high level of marine biodiversity, but its fish fauna has been poorly documented. In early studies marine species distributions were interpreted based on tectonic activity during the late Cenozoic, while more recent studies have highlighted a link with the present‐day environment. Here, we described the assemblage richness and composition of fishes in Tropical America and related these properties to both the past evolution of marine environmental conditions and current environmental gradients. Location Tropical America. Taxon Demersal and benthic fishes. Methods We mapped the distribution of 2,216 demersal and benthic fish species of Tropical America using existing occurrence data. We computed three assemblage indicators: species richness, composition and nestedness, which we explained by environmental gradients. We linked compositional distance to environmental differences using distance‐based redundancy analysis, species richness and nestedness using a generalized linear model. We ran simulations of a mechanistic model in which three processes determine the spatial dynamics of biodiversity: speciation, dispersal and extinction. This model yielded estimates for species assemblage properties following palaeogeographic changes in the region that shaped the current coastal habitat configuration. Results Fish species richness in Tropical America peaks around the Florida Peninsula, Bahamas and Greater Antilles. Fish composition varies along a depth gradient, between the Tropical Eastern Pacific and the Caribbean Sea, and forms distinct domains within the Caribbean region. The nestedness component of β‐diversity is lower in shallower assemblages, especially those along the outer section of the Greater Caribbean. Species richness and nestedness are partly explained by current environmental conditions, but model simulations illustrate how this may be further explained by the tectonic history of the region. Main conclusions Species richness peaks in the Greater Caribbean, coinciding with generally favourable current environmental conditions for demersal and benthic fishes. The high species richness and the low nestedness of fish assemblages in the Cuba region are compatible with the results of palaeo‐environmental changes that have occurred in that area. Effects of the plate tectonic history might still be present in the organization of fish fauna in this region.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Seasonal and latitudinal variation in seagrass mechanical traits across Europe: The influence of local nutrient status and morphometric plasticity - L. M. Soissons; M. M. van Katwijk; G. Peralta; F. G. Brun; P. G. Cardoso; T. F. Grilo; B. Ondiviela; M. Recio; M. Valle; J. M. Garmendia; F. Ganthy; I. Auby; et al. (Limnology and Oceanography, 2018)
Seagrasses are marine flowering plants distributed worldwide. They are however threatened, mostly due to the increase of human activities. Seagrasses have the capacity to adapt their morphological, physiological, and mechanical traits to their local conditions. Mechanical traits have been identified as a good tool to investigate a plant‐species capacity to withstand physical forces or disturbances but are still sparsely studied in seagrasses. With this study, we aimed to assess how the mechanical traits of a broadly spread seagrass species vary along a latitudinal gradient in relation to its morphometric plasticity and nutrient status. We found that seagrasses acclimate their mechanical traits in relation to their physiological or morphological traits, both over the growing season and across a latitudinal range: leaves were weaker and thinner in northern areas, particularly at the end of the growing season. Besides the influence of the latitudinal gradient, leaf mechanical strength and stiffness were both strongly affected by their morphometric plasticity. Moreover, we showed that leaves mechanical traits change depending on their nutrient status: leaves were stronger and stiffer in oligotrophic conditions as compared to more eutrophic conditions. Thus, our results imply that, under eutrophication, leaves become weaker and thus more vulnerable to physical forces. This vulnerability is higher in the north at the end of the growing season. The latter is consistent with the more ephemeral character of northern seagrass meadows, in contrast to the more evergreen southern meadows.

Modulation of the multidrug efflux pump EmrD-3 from Vibrio cholerae by Allium sativum extract and the bioactive agent allyl sulfide plus synergistic enhancement of antimicrobial susceptibility by A. sativum extract - Merissa M. Bruns; Prathusha Kakarla; Jared T. Floyd; Mun Mun Mukherjee; Robert C. Ponce; John A. Garcia; Indrika Ranaweera; Leslie M. Sanford; Alberto J. Hernandez; T. Mark Willmon; Grace L. Tolson; Manuel F. Varela (Archives of Microbiology, 2017)

Inhibition of the multidrug efflux pump LmrS from Staphylococcus aureus by cumin spice Cuminum cyminum - Prathusha Kakarla; Jared Floyd; MunMun Mukherjee; Amith R. Devireddy; Madhuri A. Inupakutika; Indrika Ranweera; Ranjana KC; Ugina ‘Shrestha; Upender Rao Cheeti; Thomas Mark Willmon; Jaclyn Adams; Merissa Bruns; et al. (Archives of Microbiology, 2017)

Heterogeneous vesiculation of 2011 El Hierro xeno-pumice revealed by X-ray computed microtomography - S. E. Berg; V. R. Troll; F. M. Deegan; S. Burchardt; M. Krumbholz; L. Mancini; M. Polacci; J. C. Carracedo; V. Soler; F. Arzilli; F. Brun (Bulletin of Volcanology, 2016)

Pollen limitation may be a common Allee effect in marine hydrophilous plants: implications for decline and recovery in seagrasses - B. I. Van Tussenbroek; L. M. Soissons; T. J. Bouma; R. Asmus; I. Auby; F. G. Brun; P. G. Cardoso; N. Desroy; J. Fournier; F. Ganthy; J. M. Garmendia; L. Godet; et al. (Oecologia, 2016)

A tailored implementation strategy to reduce the duration of intravenous antibiotic treatment in community-acquired pneumonia: a controlled before-and-after study - M. F. Engel; A. H. W. Bruns; M. E. J. L. Hulscher; C. A. J. M. Gaillard; S. U. C. Sankatsing; F. Teding van Berkhout; M. H. Emmelot-Vonk; E. M. Kuck; M. H. M. Steeghs; J. H. den Breeijen; R. K. Stellato; A. I. M. Hoepelman; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Impact of a program combining pre-authorization requirement and post-prescription review of carbapenems: an interrupted time-series analysis - T. Delory; A. Pontfarcy; A. Emirian; F. About; B. Berdougo; C. Brun-Buisson; P. Lesprit (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Towards a unified paradigm for sequence‐based identification of fungi - Urmas Kõljalg; R. Henrik Nilsson; Kessy Abarenkov; Leho Tedersoo; Andy F. S. Taylor; Mohammad Bahram; Scott T. Bates; Thomas D. Bruns; Johan Bengtsson‐Palme; Tony M. Callaghan; Brian Douglas; Tiia Drenkhan; et al. (Molecular Ecology, 2013)
The nuclear ribosomal internal transcribed spacer ( ITS ) region is the formal fungal barcode and in most cases the marker of choice for the exploration of fungal diversity in environmental samples. Two problems are particularly acute in the pursuit of satisfactory taxonomic assignment of newly generated ITS sequences: (i) the lack of an inclusive, reliable public reference data set and (ii) the lack of means to refer to fungal species, for which no Latin name is available in a standardized stable way. Here, we report on progress in these regards through further development of the UNITE database ( http://unite.ut.ee ) for molecular identification of fungi. All fungal species represented by at least two ITS sequences in the international nucleotide sequence databases are now given a unique, stable name of the accession number type (e.g. H ymenoscyphus pseudoalbidus | GU 586904| SH 133781.05 FU ), and their taxonomic and ecological annotations were corrected as far as possible through a distributed, third‐party annotation effort. We introduce the term ‘species hypothesis’ ( SH ) for the taxa discovered in clustering on different similarity thresholds (97–99%). An automatically or manually designated sequence is chosen to represent each such SH. These reference sequences are released ( http://unite.ut.ee/repository.php ) for use by the scientific community in, for example, local sequence similarity searches and in the QIIME pipeline. The system and the data will be updated automatically as the number of public fungal ITS sequences grows. We invite everybody in the position to improve the annotation or metadata associated with their particular fungal lineages of expertise to do so through the new Web‐based sequence management system in UNITE .

Genus Distichopora (Cnidaria, Hydrozoa): from primary cyclosystem to adult pore organisation - S. Puce; D. Pica; F. Brun; L. Mancini; G. Bavestrello (Coral Reefs, 2012)

Effects of fertilizers and plant strengtheners on the susceptibility of tomatoes to single and mixed isolates of Phytophthora infestans - K. Sharma; C. Bruns; A. F. Butz; M. R. Finckh (European Journal of Plant Pathology, 2012)

Mycoheterotrophic interactions are not limited to a narrow phylogenetic range of arbuscular mycorrhizal fungi - VINCENT S. F. T. MERCKX; STEVEN B. JANSSENS; NICOLE A. HYNSON; CHELSEA D. SPECHT; THOMAS D. BRUNS; ERIK F. SMETS (Molecular Ecology, 2012)
The majority of achlorophyllous mycoheterotrophic plant species associate with arbuscular mycorrhizal fungi (AMF). Previous studies have shown that some species are highly specialized towards narrow lineages of AMF and have suggested that only particular lineages of these fungi are targeted by mycoheterotrophic plants. To test this hypothesis, we analyzed all available partial SSU sequences of AMF associated with mycoheterotrophic plants including data from 13 additional specimens from French Guiana, Gabon and Australia. Sequences were assigned to ‘virtual taxa’ (VT) according to the Maarj AM database. We found that 20% of all known Glomeromycota VT are involved in mycoheterotrophic interactions and the majority of associations involve Glomeraceae ( Glomus Group A) fungi. While some mycoheterotrophic plant species have been found growing with only a single VT, many species are able to associate with a wide range of AMF. We calculated significant phylogenetic clustering of Glomeromycota VT involved in mycoheterotrophic interactions, suggesting that associations between mycoheterotrophic plants and AMF are influenced by the phylogenetic relationships of the fungi. Our results demonstrate that many lineages of AMF are prone to exploitation by mycoheterotrophic plants. However, mycoheterotrophs from different plant lineages and different geographical regions tend to be dependent on lineages of AMF that are phylogenetically related.

Assessment of the Environmental Quality of French Continental Mediterranean Lagoons with Oyster Embryo Bioassay - F. Galgani; J. Senia; J. L. Guillou; T. Laugier; D. Munaron; B. Andral; B. Guillaume; E. Coulet; P. Boissery; L. Brun; M. C. Bertrandy (Archives of Environmental Contamination and Toxicology, 2009)

Future impact of anthropogenic sulfate aerosol on North Atlantic climate - Irene Fischer-Bruns; Dorothea F. Banse; Johann Feichter (Climate Dynamics, 2009)

Interaction between hydrodynamics and seagrass canopy structure: Spatially explicit effects on ammonium uptake rates - E. P. Morris; G. Peralta; F. G. Brun; L. van Duren; T. J. Bouma; J. L. Perez-Llorens (Limnology and Oceanography, 2008)
The hypotheses that (1) different seagrass morphologies may facilitate different nutrient uptake rates under similar hydrodynamic forcing and (2) this effect on nutrient uptake rates is spatially explicit, with the highest uptake rates at edges of patches, where currents and turbulence are highest, were examined under unidirectional flow conditions. Homogeneous patches (2 m long) of two seagrass species ( Cymodocea nodosa and Zostera noltii ) with contrasting shoot size and density were placed in a race track flume. 15 NH 4 + uptake and hydrodynamic properties along a gradient from outside to inside the patch were measured at a range of current velocities (0.05 to 0.3 m s ‐1 ). For each velocity we also determined the height and bending of the canopy. Water velocity affected the ammonium uptake rate of both species. The almost double uptake rates of C. nodosa shoots, compared to those of Z. noltii , were mainly attributed to a twofold difference in the within‐canopy water flow ( Q c , m 3 s ‐1 ). Spatial patterns in canopy water flow were highly correlated with spatial patterns in NH 4 + uptake, thereby explaining the 20% higher uptake rates at the leading edge of both canopies. The correlation between spatial patterns in canopy water flow and ammonium uptake rates underlines the role of canopy and patch configuration in determining the functioning of seagrass landscapes and their associated ecosystem services, such as nitrogen assimilation.

Monitoring the assembly of antibody-binding membrane protein arrays using polarised neutron reflection - Anton P. Le Brun; Stephen A. Holt; Deepan S. Shah; Charles F. Majkrzak; Jeremy H. Lakey (European Biophysics Journal, 2008)

Detection, introgression and localization of genes conferring specific resistance to Leptosphaeria maculans from Brassica rapa into B. napus - M. Leflon; H. Brun; F. Eber; R. Delourme; M. O. Lucas; P. Vallée; M. Ermel; M. H. Balesdent; A. M. Chèvre (Theoretical and Applied Genetics, 2007)

Water-Soluble Ions and Trace Metals in Airborne Particles Over Urban Areas of the State of São Paulo, Brazil: Influences of Local Sources and Long Range Transport - Pérola C. Vasconcellos; Rajasekhar Balasubramanian; Roy E. Bruns; Odon Sanchez-Ccoyllo; Maria F. Andrade; Marlene Flues (Water, Air, & Soil Pollution, 2007)

Early detection of PrP res in BSE-infected bovine PrP transgenic mice - A. Gutiérrez Adán; A. Brun; B. Pintado; M. A. Ramírez; B. Parra; D. Doyle; M. Rogers; F. J. Salguero; J. Castilla; C. Sánchez; J. M. Sánchez-Vizcaíno; J. M. Torres (Archives of Virology, 2003)

Seasonal changes in morphology and function of the gastrointestinal tract of free-living alpine marmots ( Marmota marmota ) - Hume I.; Beiglböck C.; Ruf T.; Frey-Roos F.; Bruns U.; Arnold W. (Journal of Comparative Physiology B, 2002)

Molecular Dynamics of Biological Probes by Fluorescence Correlation Microscopy with Two-Photon Excitation - E. Guiot; M. Enescu; B. Arrio; G. Johannin; G. Roger; S. Tosti; F. Tfibel; F. Mérola; A. Brun; P. Georges; M. P. Fontaine-Aupart (Journal of Fluorescence, 2000)

Design and construction of African swine fever virus chimeras incorporating foreign viral epitopes - A. Brun; F. Rodríguez; F. Parra; F. Sobrino; J. M. Escribano (Archives of Virology, 1999)

Results of the seventh joint pesticide testing programme carried out by the IOBC/WPRS-Working Group ‘Pesticides and Beneficial Organisms’ - G. Sterk; S.A. Hassan; M. Baillod; F. Bakker; F. Bigler; S. Blümel; H. Bogenschütz; E. Boller; B. Bromand; J. Brun; J.N.M. Calis; J. Coremans-Pelseneer; et al. (BioControl, 1999)

Selection of stable Brassica napus-B. juncea recombinant lines resistant to blackleg (Leptosphaeria maculans). 1. Identification of molecular markers, chromosomal and genomic origin of the introgression - A. M. Chèvre; P. Barret; F. Eber; P. Dupuy; H. Brun; X. Tanguy; M. Renard (Theoretical and Applied Genetics, 1997)

Protoancylodiscoides malapteruri n. sp. (Monogenea, Dactylogyridea, Ancyrocephalidae), parasite branchial de Malapterurus electricus Gmelin (Siluriformes, Malapteruridae), au Cameroun - Charles F. Bilong Bilong; Emile Birgi; Nathalie Le Brun (Systematic Parasitology, 1997)

Metabolic and hormonal responses during repeated bouts of brief and intense exercise: effects of pre-exercise glucose ingestion - D. Wouassi; J. Mercier; S. Ahmaidi; J. F. Brun; B. Mercier; A. Orsetti; C. Prfaut (European Journal of Applied Physiology, 1997)

Results of the sixth joint pesticide testing programme of the IOBC/WPRS-working group «pesticides and beneficial organisms» - S. A. Hassan; F. Bigler; H. Bogenschütz; E. Boller; J. Brun; J. N. M. Calis; J. Coremans-Pelseneer; C. Duso; A. Grove; U. Heimbach; N. Helyer; H. Hokkanen; et al. (BioControl, 1994)

Results of the fifth joint pesticide testing programme carried out by the IOBC/WPRS-Working Group “Pesticides and beneficial organisms” - S. A. Hassan; F. Bigler; H. Bogenschütz; E. Boller; J. Brun; J. N. M. Calis; P. Chiverton; J. Coremans-Pelseneer; C. Duso; G. B. Lewis; F. Mansour; L. Moreth; et al. (BioControl, 1991)

Lymphocytic choriomeningitis virus - G. Mller; M. Bruns; Liliana Martnez Peralta; F. Lehmann-Grube (Archives of Virology, 1983)

Ultrastructural studies on Maedi-Visna virus - F. Weiland; M. Bruns (Archives of Virology, 1980)

Some aspects of metabolic activation of chemical carcinogens in relation to their organ specificity - H. Bartsch; G. P. Margison; C. Malaveille; A. M. Camus; G. Brun; J. M. Margison; G. F. Kolar; M. Wiessler (Archives of Toxicology, 1977)